Post-exercise rehydration: The protocol for distributing a fixed fluid volume intake does not change fluid conservation - Alexandra Pérez Idárraga; Luis Fernando Aragón Vargas (Universidad de Costa Rica, 2011)
Purpose: To evaluate the effectiveness of three sports drink intake protocols on post-exercise rehydration, as measured by fluid retention in the body. Methods: On three separate days, one week apart, 11 healthy, physically active men (age = 21 ± 2 y, weight = 68.7 ± 9.0 kg, and height = 1.72 ± 0.05 m) were dehydrated by 1.97 ± 0.20% body mass (mean±S.D.) by exercising in a controlled environment chamber at approximately 32úC and 60% relative humidity. They were rehydrated with a volume of sports drink equivalent to 120% of body mass (BM) loss, distributed according to one of three intake protocols: constant (CON), three equal aliquots equivalent to 40% of BM loss each; ascending (AS) aliquots of 25, 40, and 55%; or descending (DES) aliquots of 55, 40, and 25%. They drank one portion every 30 minutes, over 1.5 hours; the order of treatments was assigned at random. Urine was collected at the end of rehydration and every 30 minutes over three hours for volume measurements. Results were analyzed using repeated-measures ANOVAs. Results: There was no interaction between intake protocol and time on partial urine volumes (p=.119). There was no effect of intake protocol on total urine volume (CON=670±278 mL, AS=649±184 mL, DES=750±421 mL; p=.609) or on fluid retention (CON=59.0±16.1%, AS=59.7±13.7%, DES=54.9±19.9%; p=.835). Conclusion: Distribution of a fixed volume of sports drink into three different post-exercise rehydration protocols resulted in no significant differences in urine volume, or in fluid retention.